The repercussions of unilateral economic sanctions on the Syrian economy "US sanctions as a model" - سليّمانو رشا; يوسف محمود; إيهاب عليا (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Economic sanctions are considered one of the most prominent non-military means used by major countries as a tool to implement their political and economic plans. The United States of America has often followed this method against countries that violate its policy and the approach it is following. Syria is considered a clear example as the United States of America has tried to subjugate it in a way that... It is consistent with its political and economic goals, but Syria’s rejection of this made it a primary target for it to impose these illegal unilateral sanctions on it from 1979 until now, citing several arguments. It sometimes tended to accuse Syria of supporting terrorism and at other times under the pretext of protecting Syrian citizens and others. Among the unacceptable arguments, the most prominent of these sanctions was the American Caesar Act, whose provisions included all economic sectors and all partners that could have provided support to Syria, especially in light of the global war against it. All of this had a negative impact on the most prominent indicators of the Syrian economy, such as the gross domestic product, and in turn, this robbed the Syrian citizen of his most basic rights, such as his right to obtain food and shelter and his right to live in dignity. Therefore, there was an urgent need to study the impact of these unilateral sanctions on Syria in general, and on the citizen. Syrians in particular.